Burnout Karyawan di PT Harian Rakyat Bengkulu Pers - Praningrum, Praningrum; Ariyadi, Ariyadi (Universitas Muhammadiyah Yogyakarta, 2010)
The reasearch objective was “to investigate the influence of psycological working environment, job promotion, wages, social support from corporation, and the demands of work on the editorial staff burnout at PT Harian rakyat Bengkulu either simultaneously or partially.Data used in this study are primary data obtained by qustionire. The sampling technique used was purposive sampling methode by taking all the employees that Bengkulu People’s Daily editorial PT Bengkulu Press as many as 35 people.The result showed that the psycological work environment factors, promotion, wages, social support from superiors, and the demands of work had significant and negative effect on employee burnout in PT Bengkulu Press People’s Daily. Variable contribution amounted to 76,5% while the rest of 23,5% influenced by other factors not included in this study.